ダイ8ジ ナンキョク チイキ カンソク エットウタイ ウチュウセン ブモン ホウコク ウチュウセン チュウセイシ レンゾク カンソク - 石田, 喜雄; イシダ, ヨシオ; 小玉, 正弘; コダマ, マサヒロ; ISHIDA, Yoshio; KODAMA, Masahiro (国立極地研究所, 1969)
P(論文) At Syowa Station, Antarctica, the cosmic-ray neutron observation was made, at the initial stage, with the IGY-type neutron monitor during the period from March 1960 to December 1961. On the opportunity of IQSY, a new type of cosmic-ray meter, IQSY-type neutron monitor, was developed by CARMICHAEL. In February 1967, the IQSY-type neutron monitor consisting of three counters (3-NM-64) was installed at Syowa Station in the 8th Japanese Antarctic Research Expedition. In February 1968 seven counters were added and two more in February 1969, finally twelve counters. The recording system for observation comprises the so-called multiplicity meter, by which the counting rates are divided into six channels, multiplicity=1 to more than 6, according to the neutron multiplicity detected within the gating time of 1 m sec. The counting rates are automatically printed and punched on a tape every ten minutes. This readout equipment became duplex since February 1968. The cosmic-ray observation room was specially designed so as to avoid influence of snowdrift around the building in which the neutron monitor is installed, and also to keep the room temperature constant throughout the year. In practice, no snow effect on the neutron intensity was recognized and the room temperature was 20°±1℃ in 1967. This report describes details of the cosmic-ray neutron observation in 1967-1968 and some results deduced from data analyses The atmospheric effect, the diurnal variation and the Forbush decrease were investigated in connection with the neutron multiplicity, particularly with regard to the remarkable Forbush event in May 1967. departmental bulletin paper